2006
DOI: 10.1007/s00262-006-0213-z
|View full text |Cite
|
Sign up to set email alerts
|

Ii-Key/HER-2/neu(776-90) hybrid peptides induce more effective immunological responses over the native peptide in lymphocyte cultures from patients with HER-2/neu+ tumors

Abstract: We have demonstrated that coupling an immunoregulatory segment of the MHC class II-associated invariant chain (Ii), the Ii-Key peptide, to a promiscuous MHC class II epitope significantly enhances its presentation to CD4+ T cells. Here, a series of homologous Ii-Key/HER-2/neu(776-790) hybrid peptides, varying systematically in the length of the epitope(s)-containing segment, are significantly more potent than the native peptide in assays using T cells from patients with various types of tumors overexpressing H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
38
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
3
3

Relationship

3
3

Authors

Journals

citations
Cited by 46 publications
(39 citation statements)
references
References 42 publications
1
38
0
Order By: Relevance
“…41,42 We also observed strong immunogenicity with HER-2/neu(776-790), which is an extended analog of the p776 to p788 peptide. [43][44][45] CD4-positive T cells primed with the p776 to p790 peptide exhibited an extensive capacity to synergize with syngeneic CTLs for the rejection of HER-2/neu-positive tumors. [43][44][45] Both the p776 to p790 peptide and the p776 to p788 peptide encompass in their sequences the nonamers GVGSPYVSRL (p776-p784), VGSPYVSRL (p777-p785), and PYVSRLLGI (p780-788), which bind with intermediate to high affinity to the HLA-A2.1/A68, HLA-A11, and HLA-A3 alleles, respectively.…”
Section: Immunogenic Her-2/neu Peptides and Ii-key/her-2/neu Hybrid Pmentioning
confidence: 99%
See 1 more Smart Citation
“…41,42 We also observed strong immunogenicity with HER-2/neu(776-790), which is an extended analog of the p776 to p788 peptide. [43][44][45] CD4-positive T cells primed with the p776 to p790 peptide exhibited an extensive capacity to synergize with syngeneic CTLs for the rejection of HER-2/neu-positive tumors. [43][44][45] Both the p776 to p790 peptide and the p776 to p788 peptide encompass in their sequences the nonamers GVGSPYVSRL (p776-p784), VGSPYVSRL (p777-p785), and PYVSRLLGI (p780-788), which bind with intermediate to high affinity to the HLA-A2.1/A68, HLA-A11, and HLA-A3 alleles, respectively.…”
Section: Immunogenic Her-2/neu Peptides and Ii-key/her-2/neu Hybrid Pmentioning
confidence: 99%
“…[43][44][45] CD4-positive T cells primed with the p776 to p790 peptide exhibited an extensive capacity to synergize with syngeneic CTLs for the rejection of HER-2/neu-positive tumors. [43][44][45] Both the p776 to p790 peptide and the p776 to p788 peptide encompass in their sequences the nonamers GVGSPYVSRL (p776-p784), VGSPYVSRL (p777-p785), and PYVSRLLGI (p780-788), which bind with intermediate to high affinity to the HLA-A2.1/A68, HLA-A11, and HLA-A3 alleles, respectively. Thus, the p776 to p790 peptide may function as a multipeptide vaccine that contains overlapping T h and CTL epitope motifs, thereby acting as a powerful inducer of antitumor immune responses.…”
Section: Immunogenic Her-2/neu Peptides and Ii-key/her-2/neu Hybrid Pmentioning
confidence: 99%
“…19). To assess whether immune responses elicited in vivo reflected reactivity against the native HER-2/ neu peptide, we evaluated immune responses against both AE36 and AE37.…”
Section: Peptides and Proteinsmentioning
confidence: 99%
“…Covalent linkage of this Ii-Key segment to MHC class II epitopes significantly augments antigen presentation (13)(14)(15)(16). Work from our laboratory has shown that the HER-2/neu(776-790) epitope serves as a compelling tumor antigen and that CD4 + T cells primed with the synthetic HER-2/neu(776-790) peptide help autologous CTL for increased antitumor activity (17)(18)(19). In a series of studies (14,(17)(18)(19)(20), we have shown that the Ii-Key/ HER-2/neu(776-790) hybrid (AE37) induces more potent immunologic responses both in vitro and in vivo compared with the nonmodified HER-2/neu(776-790) peptide (AE36).…”
mentioning
confidence: 99%
See 1 more Smart Citation